Model Pengelolaan Kelas Dengan Team Teaching Pada Pembelajaran Ilmu Pengetahuan Sosial KELAS VIII SMP Muhammadiyah Program Khusus Kota Barat Surakarta - Wulandari, Indah, Agus Susilo, S.Pd., M.Pd (2017)
This qualitative research aims to determine the concept of learning with team teaching, the implementation of classroom management with team teaching, and the results obtained in learning with team teaching in class VIII SMP Muhammadiyah Program Khusus Kota Barat Surakarta. Data collection hniques used in research are interviews, observation, and documentation.Technique of data analysis using method which cover analysis before in field; Data analysis in the field that includes data reduction, data presentation, and conclusions or verification, and data analysis during the field with taxonomic analysis. Based on the results of research can be concluded that social science learning class VIII SMP Muhammadiyah Program Khusus Kota Barat Surakarta implement semi- team teaching which belongs to the Monitoring Teacher Model where the teaching of this model is one of the teachers will monitor the progress of the student while one explains the student's learning.